Pengaruh Pemberian Rumput Lapangan dan Daun Lamtoro Gung Terhadap Konversi Ransum Kelinci Lokal Jantan (Erictolagus cuniculus) / The Effect of Field Grass and Lamtoro Gung Leaf on The Feed Conversion of Local Male Hare (Erictolagus cuniculus) - Kastalani Kastalani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
This study aims to determine the effect of field grass and leaf of lamtoro gung on the feed conversion of local male hare. This experiment using completely randomized device (CRD), with five treatment and four replications. The result showed that with the use of field grass and leaf of lamtoro gung had be significant effect on the feed conversion.